A novel approach for skin suit aerodynamic optimization using local momentum deficit - Terra, W.; Sciacchitano, A.; Scarano, F. (Proceedings, 2018)
A new approach is introduced to evaluate the potential drag reduction by skin suit design in speed sport. The approach relies upon local flow information measured in the wake of a cyclist mannequin. Lagrangian Particle Tracking is employed to measure the distribution of time-average streamwise velocity in a cross-plane of 30 × 100 cm2 behind the stretched leg of the rider at a range of Reynolds numbers (0.4 × 105 < Re < 2.4 × 105). The expected Reynolds number effect is observed: a general wake narrowing at increasing speed. Unexpected local effects are also identified, which may be due to local variations in geometry of the rider`s leg. The conservation of momentum within a control volume containing the leg is used showing that the aerodynamic drag of the rider`s leg can be decreased by application of surface roughness. This outcome is validated by repeated measurements using zigzag tape on the legs` surface